Commodification of Gamelan Selonding in Tenganan Pegringsingan Village, Bali - Suharta, I Wayan (Harmonia: Journal of Arts Research and Education, 2022)
Gamelan Selonding is a form of traditional music found in Tenganan Pegringsingan village, with a pelog tujuh nada in barungan alit classification that is sacred, unique, and deeply rooted in the community. The traditional way of life and productive religious activities with their numerous manifestations ensure Gamelan Selonding’s continuity and authenticity. According to historical dynamics, the influence of external culture and its various modernization styles disrupted Gamelan Selonding’s existence, resulting in its commodification. The commodification of Gamelan Selonding is a process that encompasses three stages, namely production, distribution, and consumption. In production, Gamelan Selonding is duplicated into a commodity by imitating its original form; distribution is an attempt to spread Gamelan Selonding production, which increases development consequences; and consumption Gamelan Selonding is used as a ritual compliment and an artistic medium. The Gamelan Selonding’s commodification occurs due to its adaptable nature; it can accept, absorb, and adapt to changing circumstances, resulting in a diversity of functions, not limited to ritual contexts, but a broader social context. The commodification of Gamelan Selonding is an artistic dynamic that empowers the potential of traditional arts in the formulation of contemporary performing arts expressions, accepted as a local spectacle capable of competing in a global culture.